Minds and Behaviors at Work : Boosting Socioemotional Skills for Latin America’s Workforce - Cunningham, Wendy (World Bank, Washington, DC, 2016)
Although the Latin American region has shown an impressive growth in educational attainment over the past two decades, that education has failed to yield expected benefits. A mounting body of research and policy debates argues that the quantity of education is not an adequate metric of human capital acquisition. Rather, individuals’ skills—what they actually know and can do—should stand as policy targets and be fostered across the life course. Evidence from around the world shows that both cognitive and socio-emotional skills are demanded by employers and favorably affect a range of outcomes, including educational attainment and employment outcomes.